Drug-Coated Balloon for the Treatment of Nonacute Symptomatic Intracranial Carotid Artery Terminus Occlusion: Initial Experience and Follow-Up Outcome - Yin, Hao; Zhang, Jinping; Zhao, Wei; Zheng, Meimei; Song, Yun; Sun, Lili; Zhang, Jun; Han, Ju (Frontiers in Neurology, 2022)
Background Studies on the recanalization for occlusion of the internal carotid artery terminus are scattered. Recently, drug-coated balloon (DCB) has been increasingly applied in the intracranial artery occlusion and achieved encouraging results. However, there seems no convincing data for the nonacute symptomatic internal carotid artery terminus occlusion (sICATO). Objective To assess the feasibility and effectiveness (safety) of DCB for patients with nonacute sICATO refractory to medical therapy. Approach This study included 30 patients with nonacute sICATO treated with DCBs and/or remedial stenting. The rate of successful recanalization, periprocedural complications, and clinical and vascular imaging follow-up outcomes were retrospectively analyzed. Results Drug-coated balloon (DCB) dilatation of nonacute sICATO gives a 100% rate of successful recanalization, with a low complication rate (10.00%), good clinical outcomes (86.20%), low restenosis/reocclusion rate (3.45%), and one asymptomatic ipsilateral infarction (3.45%). Conclusion Drug-coated balloon dilation seems to be the promising treatment option for nonacute sICATO considering its safety and feasibility.